Drivers420.com : organising transporters - Ghura, Amarpreet K. Singh, (SAGE Knowledge. Cases., 2016)
This case describes a situation in which Malkit Singh Bal (Bal), partner of Bal Roadlines, shares with Mr. Ghura, who was about to be hired as consultant for Bal Roadlines, the rise in fraud and crime by the fleet drivers and asks him to help solve the problem. The purpose of this case is to provide an opportunity to the participants of an MBA or Management Executive Education Programme to step into the shoes of Ghura, a consultant, to explore the options, and to select the best possible option to offer a solution to Bal. The context for this involvement is the rise in fleet driver fraud and crime.